CASPR-2 Antibody Associated Autoimmunity in the Setting of COVID-19 (Infection, Vaccination, or Both?) and Chronic Lymphocytic Leukemia: Case Report and Review of the Literature. (5th December 2022) - Sattarnezhad, Neda; McDonald, Jamie; Tomczak, Anna; Sumera, Julia; Loeffler, Jacob; Han, May
Abstract : Objective: To report a case of Anti-Contactin-Associated Protein-like2 (CASPR-2) autoimmunity in a patient with low-grade Chronic Lymphocytic Leukemia (CLL) following COVID-19 vaccination and infection. Background: Anti-CASPR2 antibody disorder has been associated with neoplastic disorders like thymoma. Recent reports enlist COVID-19 as apotential trigger of CASPR2 autoimmunity. While the clinical presentations are similar, management differs based on the underlying etiology. Design/Methods: We review a case of anti-CASPR2-antibody associated disorder with concurrent low grade CLL and recent history of COVID-19 vaccination and infection. Additionally, we review the literature and discuss the therapeutic challenges. Results: A 73-years old male presented with five months of progressive fatigue, weight loss, diffuse sweating, muscle cramps, and neuropathic pain. He eventually developed bilateral upper and lower facial weakness. Patient contracted a mild COVID-19 infection two months prior and COVID-19 vaccination one month prior to his symptom onset. His exam was remarkable for bilateral facial weakness, diffuse fasciculations and sensory neuropathy on his trunk and extremities. His diagnostic work up including bone marrow biopsy was consistent with a chronic lymphocytic leukemia (CLL)-like immunophenotype. Cerebrospinal fluid (CSF) analysis was remarkable for five WBC (lymph-dominant) and protein of 74 mg/dl. Serum paraneoplastic panel revealed positive CASPR2 antibody with a titer of 1:100. Magnetic Resonance Imaging (MRI) of the brain showed enhancement of bilateral cranial nerve VII. After lack of clinical response to IV methylprednisone (1 gram for 5 days), patient was treated with a single cycle of IV immunoglobulin (IVIG). He had complete recovery of his symptoms except for residual facial weakness. He remains stable at his six months post-treatment follow-up. Conclusions: Anti-CASPR2 associated autoimmunity following COVID-19 infection or in the setting of CLL has previously been reported. However, cranial neuropathy in association with CASPR2 antibody has never been. A trial of IVIG could be beneficial in patients with viral-spike protein-induced autoimmunity and CLL who do not otherwise meet the criteria for CLL treatment.